Efektivitas Media Pembelajaran Interaktif dalam Mengajarkan Asmaul Husna Kepada Anak di Ar Raziq Care Center Malaysia - Anita Syafitri Zulfi; Zailani (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The purpose of this research is to investigate how well interactive learning materials educate Asmaul Husna to kids at Ar Raziq Care Center Malaysia. For young children, interactive educational materials provide a more interesting and pleasurable way to understand abstract ideas like Allah's qualities. The study used a descriptive qualitative approach, gathering data via observations, interviews, and documentation. Teachers and kids at the Ar Raziq Care Center served as the study subjects. The findings showed that children's interest and active engagement in the learning process, as well as their comprehension of Asmaul Husna, were greatly enhanced by the use of interactive technology. The media also helped teachers by enabling more efficient and interesting information delivery. As a result, interactive learning materials have shown themselves to be a useful instrument in Islamic religious education, especially when it comes to educating young students Asmaul Husna.